Q. 13.8( 4 Votes )

Write the princip

Answer :

We know that:


tan-1x + cot-1x = π/2


and cot-1(-x) = π – cot-1 x


tan-1(√3) - cot-1(-√3) = tan-1(√3) –{π - cot-1(√3)}


tan-1(√3) - cot-1(-√3) = -π + tan-1(√3) + cot-1(√3)


tan-1(√3) - cot-1(-√3) = -π + π/2 = -π/2


tan-1(√3) - cot-1(-√3) = -π/2


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

State True or FalMathematics - Exemplar

State True or FalMathematics - Exemplar

Fill in the blankMathematics - Exemplar

Fill in the blankMathematics - Exemplar

Find the principaRD Sharma - Volume 1

State True or FalMathematics - Exemplar

State True or FalMathematics - Exemplar